Study on Automotive Driveline System with Torque Converter Clutch under Harmonically Varying Normal Load - Md Din, Mohd Hazwan (Universiti Teknologi Petronas, 2008)
In this research project, an Automotive Driveline System with Torque Converter Clutch under effects of a harmonically varying normal load on transient responses of a 2-Degree Of Freedom torsional system is studied. An inunediate application of this study is the slipping torque converter clutch that is employed in automotive driveline system. The purpose of Torque Converter Clutch is to transmit rotating power from the prime movers (internal combustion engine) to the rotating driven load. Up to 10 percent of the engine energy is wasted by torque converter slipping caused by negative slope introduced by substantial stick slip motion. Investigation on key parameters that control the clutch engagement rate and pronounce the stick slip motion could further attenuate such motion. The objectives of this project is to develop its mathematical model, the system is supposed to be 2-Degree of Freedom torsional system with non-linear dry friction. Under this mathematical model, the governing equation that represents the dynamics of the system and non-linear time varying dry friction formulation is established. Then the development of MA TLAB progranuning to simulate the dynamics of the system is established. From the numerical simulation in MATLAB programming, transient responses including pure slip and stick slip transient response of the system under a harmonically varying load and sinusoidal torque excitation will be studied computationally. The effects of saturation friction torque, mean torque and engine inertia on clutch engagement rate are found significant in pure slip transient response. Furthermore, the effects of kinetic friction, saturation friction torque and phase lag on the stick-slip transient response Gudder) influence the dynamics of the system by the introduction of stick slip motion.